Work and Organizational Psychology Looks at the Fourth Industrial Revolution: How to Support Workers and Organizations? - Ghislieri, Chiara; Molino, Monica; Cortese, Claudio G. (Frontiers in Psychology, 2018)
With rapid advances in technology in several fields of human life, we are entering the Fourth Industrial Revolution, which is changing the way businesses create value, people do their work and individuals interact and communicate with each other. In this framework, many questions have arisen about how these transformations affect workers, organizations and societies, and Work and Organizational Psychology has been called upon to address some of these open issues. In particular, this article focuses on two aspects of the Fourth Industrial Revolution. The first considers the expansion of automation in the workplace and raises questions such as: how is the relationship between workers and technology changing? How is it affecting people’s well-being? How can we expect it to affect employment and equality in the future? The second is related to how job transformation will influence requirements for knowledge and skills; the main question is: which competence profile, considering hard and soft skills, is required and expected in the work of the future? The aim of the present paper is to improve the understanding of some of the major issues that workers and organizations are, or will be, asked to face, by providing information that will be useful to facilitate debate, research and interventions. In the conclusion section, research and practical implications at organizational, political and institutional levels are discussed.